Insight into the Therapeutic Potential of a Bicyclic Hydroxypyridone Compound 2‐[(2, 4‐Dichlorophenyl)methyl]‐7‐hydroxy‐1, 2, 3, 4‐tetrahydro‐8H‐pyrido[1, 2‐a]pyrazin‐8‐one as COMT Inhibitor in the Treatment of Parkinson's Disease: A Molecular Dynamic Simulation Approach. Issue 9 (9th August 2021) - Subair, Temitayo I.; Akawa, Oluwole B.; Soremekun, Opeyemi S.; Olotu, Fisayo A.; Soliman, Mahmoud E. S.
Abstract: Parkinson's disease (PD) is one of the most targeted neurodegenerative diseases in clinical research. Awareness of research is due to its increasing number of affected people worldwide. The pathology of PD has been linked to several key proteins upregulation such as the catechol O‐Methyltransferase (COMT). Hence, the synthesis of compounds possessing inhibitory capacity has been the frontline of research in recent years. Several compounds have been synthesized among which is the nitrocatechol. However, major limitations associated with the nitrocatechol scaffold include the inability to possess adequate CNS penetration properties and hepatic toxicity associated with the compounds. However, a series of bicyclic hydroxypyridones compounds were synthesized to evaluate their inhibitory potentials on COMT protein with compound 38 (c38) 2‐[(2, 4‐dichlorophenyl)methyl]‐7‐hydroxy‐1, 2, 3, 4‐tetrahydro‐8 H ‐pyrido[1, 2‐ a ]pyrazin‐8‐one shown to have a 40 fold increase level coverage in its IC50 over brain exposure when compared to the other synthesized compound. The molecular dynamics method was employed to understand the nature of interaction exhibited by c38. Molecular mechanics of c38 revealed a disruptive effect on the secondary structure of COMT protein. Per residue decomposition analysis revealed similar crucial residues involved in the favorable binding of c38 and tolcapone implicated its increased inhibitory capacity on COMT in preventing PD. Free binding energy (Δ Gbind ) of c38 further revealed the inhibitory capacity towards COMT protein in comparison to the FDA approved tolcapone. Ligand mobility analysis of both compounds showed a timewise different mobility pattern across the simulation time frame at the active site pocket of the protein connoting the different inhibitory potency exhibited by c38 and tolcapone. Findings from this study revealed optimization of c38 could facilitate the discovery of new compounds with enhanced inhibitory properties towards COMT in treating PD. Abstract :